A Dual‐Response Fluorescent Probe Reveals the H2O2‐Induced H2S Biogenesis through a Cystathionine β‐Synthase Pathway. Issue 43 (4th September 2015) - Yi, Long; Wei, Lv; Wang, Runyu; Zhang, Changyu; Zhang, Jie; Tan, Tianwei; Xi, Zhen
Abstract: The two signaling molecules H2 S and H2 O2 play key roles in maintaining intracellular redox homeostasis. The biological relationship between H2 O2 and H2 S remains largely unknown in redox biology. In this study, we rationally designed and synthesized single‐ and dual‐response fluorescent probes for detecting both H2 O2 and H2 S in living cells. The dual‐response probe was shown to be capable of mono‐ and dual‐detection of H2 O2 and H2 S selectively and sensitively. Detailed bioimaging studies based on the probes revealed that both exogenous and endogenous H2 O2 could induce H2 S biogenesis in living cells. By using gene‐knockdown techniques with bioimaging, the H2 S biogenesis was found to be majorly cystathionine β‐synthase (CBS)‐dependent. Our finding shows the first direct evidence on the biological communication between H2 O2 (ROS) and H2 S (RSS) in vivo. Abstract : CBS is responsible : A fluorescent probe with two heads for H2 O2 and H2 S reveals that both exogenous and endogenous H2 O2 molecules can induce endogenous H2 S biogenesis on a cystathionine β‐synthase (CBS) pathway (see scheme).